A Beautiful Equation

Algebra Level 4

2 x + 3 y = 7 2x+3y=7 and a ( x + y ) b ( x y ) = 3 a + b 2 a(x+y)-b(x-y)=3a+b-2 .

For what values of a a and b b does the above pair of equations have an infinite number of solutions?

Write the solution as a 2 + 2 a b + b 2 a^2+2ab+b^2 .

This problem is original.


The answer is 36.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Jun 21, 2015

{ 2 x + 3 y = 7 a ( x + y ) b ( x y ) = 3 a + b 2 { 2 x + 3 y = 7 ( a b ) x + ( a + b ) y = 3 a + b 2 \begin{cases} 2x + 3y = 7 \\ a(x+y)-b(x-y) = 3a+b-2 \end{cases} \\ \Rightarrow \begin{cases} 2x + 3y = 7 \\ (a-b)x+(a+b)y = 3a+b-2 \end{cases}

For the two equations to have infinite solutions, they must be identical.

{ a + b a b = 3 2 2 a + 2 b = 3 a 3 b a = 5 b 3 a + b 2 a b = 7 2 32 b 4 = 28 b b = 1 a = 5 \Rightarrow \begin{cases} \dfrac {a+b}{a-b} = \dfrac{3}{2} & \Rightarrow 2a+2b = 3a-3b & \Rightarrow a = 5b \\ \dfrac {3a+b-2}{a-b} = \dfrac {7}{2} & \Rightarrow 32b - 4 = 28 b & \Rightarrow b = 1 & \Rightarrow a = 5 \end{cases}

We note that substituting a = 5 a=5 and b = 1 b=1 in the second equation we have:

( a b ) x + ( a + b ) y = 3 a + b 2 (a-b)x+(a+b)y = 3a+b-2

4 x + 6 y = 14 \Rightarrow 4x + 6y = 14 identical to 2 x + 3 y = 7 2x+3y = 7

Therefore, a 2 + 2 a b + b 2 = ( a + b ) 2 = ( 5 + 1 ) 2 = 36 a^2 +2ab + b^2 = (a+b)^2 = (5+1)^2 = \boxed{36}

Nice solution sir. we can solve it by properties of ratios of coefficients of simultaneous equations.

A Former Brilliant Member - 5 years, 11 months ago
Tijmen Veltman
Jun 21, 2015

We can rewrite the system as:

2 x + 3 y = 7 ( a b ) x + ( a + b ) y = 3 a + b 2. \begin{aligned} 2x +3y &=7\\ (a-b)x +(a+b)y &=3a+b-2. \end{aligned}

This system will always have 1 solution, unless the two equations on the left hand side are proportional (i.e. the matrix of coefficients has determinant zero). Hence we require:

2 × ( a + b ) = 3 × ( a b ) a = 5 b . 2\times(a+b)=3\times(a-b)\Rightarrow a=5b.

If we substitute this and multiply the first equation by 2 b 2b , we obtain:

b ( 4 x + 6 y ) = 14 b b ( 4 x + 6 y ) = 16 b 2 \begin{aligned} b(4x+6y)&=14b\\ b(4x+6y)&=16b-2 \end{aligned} .

This only has solutions if 14 b = 16 b 2 14b=16b-2 and so b = 1 b=1 and a = 5 a=5 . Hence we get a 2 + 2 a b + b 2 = 5 2 + 2 5 1 + 1 2 = 36 a^2+2ab+b^2=5^2+2\cdot 5\cdot 1+1^2=\boxed{36} .

In this case, both equations are equivalent and we see that any pair ( x , y ) (x,y) on the line y = 1 3 ( 7 2 x ) y=\frac13(7-2x) is a solution.

Nice solution .

A Former Brilliant Member - 5 years, 11 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...